Pengaruh Kemampuan Finansial dan Aksesibilitas Terhadap Minat Siswa untuk Melanjutkan Pendidikan ke Perguruan Tinggi - Ika Wisudawaty; Adiningsih S, Sri Hutami (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The purpose of this study is to analyze how financial capability and accessibility influence the interest of students at the UPTD SMAN 2 Campalagian, particularly those living in Rumpa Village, to pursue higher education. Economic barriers and access issues, such as distance and transportation, are the main obstacles affecting students' interest in continuing their education. This study used a descriptive quantitative method and collected data through questionnaires and documentation. Based on rational choice theory (Coleman, 1990), students' decisions to continue their education are heavily influenced by a cost-benefit analysis related to costs and accessibility. The findings of this study indicate that financial capability and accessibility significantly influence student interest, with financial capability being the most influential factor. It is hoped that these results can be used as a basis for formulating inclusive education policies for students in rural areas.